Analisis Gaya Bahasa Pada Lirik Lagu Dalam Album “Manusia” Karya Tulus - Haedariah, Haedariah; Alan; Anggun Kasmarita (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
Stylistic Analysis of Song Lyrics in the Album "Manusia" by Tulus. Department of Indonesian Language and Literature Education. The formulation of the problem in this study is what language styles are used in the song lyrics on the album "Manusia" by Tulus? This study aims to identify what language styles are contained in the lyrics of songs in the album "Manusia" by Tulus. This type of research is literature research. The method used in this study is the descriptive method. The data in this study is in the form of words or sentences that contain language style. The source of data used in this study was ten songs contained in the album "Manusia" by Tulus obtained from CD and Tulus's official yotube account. The data collection techniques used are documentation techniques and hermeneutic techniques. The data analysis technique used is a stylistic approach. The results of this study showed that metaphorical language styles, personification, hyperbole, anticlimax, apostrophe, anastrof or inversion, cynicism, erothesis, anaphora, epistropha, simploke, mesodiplosis, epanalepsis, and anadiplosis were found. The most dominant language style is anaphora language style.